Evaluation of Left Ventricular Diastolic Function by Echocardiography with Tissue Doppler in Systemic Sclerosis - Roque,Marina Carneiro de Freitas (2017)
Abstract Background: Systemic sclerosis (SS) is a connective tissue abnormality characterized by fibrosis of the skin and internal organs. Cardiac involvement with consequent myocardial dysfunction in SS is associated with increased morbidity and mortality. Objective: To investigate the left ventricular (LV) diastolic function in patients with SS and preserved systolic function. Methods: Patients with SS were evaluated with two-dimensional echocardiography with tissue Doppler for analysis of chamber diameters, LV mass index (LVMI), indexed left atrial volume (iLAV), systolic function of both ventricles, and presence and degree of diastolic dysfunction (DD). Results: We evaluated 50 patients, divided according to the presence of DD into Group 1 (n = 25; normal diastolic function, E/A ratio ≥ 0.8, deceleration time [DT] > 150 ms and < 200 ms, and septal e’ > 8 cm/s) and Group 2 (n = 25; with DD, subdivided into type I DD [E/A < 0.8, DT > 200 ms], type II [E/A ≥ 0.8, septal e’ < 8 cm/s, iLAV > 34 mL/m2], and type III [E/A > 2, DT < 150 ms, septal e’ < 8 cm/s]). Type I DD was the most frequent (34%), followed by type II DD (16%). LVMI and iLAV were similar in both groups, but septal and lateral e’ were reduced only in Group 2. In Group 2, we observed that patients with moderate DD had longer disease duration (p = 0.02). Conclusion: The prevalence of type I DD was elevated in SS and associated with aging. Disease duration emerged as an important factor in moderate DD.